2019
DOI: 10.1002/jat.3817
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects and involved molecular pathways of nanoparticles on cells and subcellular organelles

Abstract: Owing to the increasing application of engineered nanoparticles (NPs), besides the workplace, human beings are also exposed to NPs from nanoproducts through the skin, respiratory tract, digestive tract and vein injection. This review states pathways of cellular uptake, subcellular distribution and excretion of NPs. The uptake pathways commonly include phagocytosis, micropinocytosis, clathrin‐ and caveolae‐mediated endocytosis, scavenger receptor‐related pathway, clathrin‐ or caveolae‐independent pathway, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 151 publications
2
65
0
3
Order By: Relevance
“…Besides, lysosome impairment and autophagy dysfunction are attracting growing attention for SiNPs-induced damages [8,9]. Lysosomes contain diverse acidic hydrolases, such as cathepsins, and nanoparticles are reported to accumulate in the lysosomes by endocytosis and subsequently induce cathepsin-dependent inflammation [10]. Recent studies suggest that NPs induce activation of the NLRP3 inflammasome and generation of interleukin-1β (IL-1β) via lysosomal rupture and consequent release of cathepsins [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, lysosome impairment and autophagy dysfunction are attracting growing attention for SiNPs-induced damages [8,9]. Lysosomes contain diverse acidic hydrolases, such as cathepsins, and nanoparticles are reported to accumulate in the lysosomes by endocytosis and subsequently induce cathepsin-dependent inflammation [10]. Recent studies suggest that NPs induce activation of the NLRP3 inflammasome and generation of interleukin-1β (IL-1β) via lysosomal rupture and consequent release of cathepsins [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that NM exposure could induce ER stress of cells, which consequently leads to the activation of apoptosis pathway 19. Meanwhile, NM-induced oxidative stress might also lead to prolonged ER stress 19,20. For MWCNTs, we recently showed that MWCNTs could activate ER stress in HUVECs, which is related with the lengths12 and diameters13 of MWCNTs.…”
Section: Methodsmentioning
confidence: 94%
“…Considering that suppression of cell growth influences the increase in uptake rate of MWCNT, the uptake rate of CNHs is actually highest. We have reported that intracellular uptake of MWCNT in non-phagocytic cell lines may be due to three types of endocytosis as well as uptake by alternative pathways [50], and Liu et al, recently published a review of intracellular uptake of nanoparticles [51]. However, the molecular mechanism by which cells first recognize nanomaterials remains unclear.…”
Section: Discussionmentioning
confidence: 99%